KEBIJAKAN ANGGARAN PERTAHANAN NASIONAL DI SETIAP REJIM PEMERINTAHAN INDONESIA - Kennedy, Posma Sariguna Johnson (Fakultas Ekonomi Universitas Kristen Indonesia, 2017)
The development of defense forces is always confronted with the problem of resource constraints, including national funding sources that are faced with other priority national policy options. This paper presents the Indonesian defense doctrine and views of the threats experienced in every era of regim in Indonesia. We also, will be described the history of Indonesian defense, and a description of the threats and ambitions of the new order (Orde Baru) to the order of reform (Orde Reformasi). The research method is the literature review of various library materials. In every era of leadership Indonesia always has a desire to be the best in the international region. The priority on the economy is the direction in developing the national power. Because a country that has great economic power is certainly able to develop the welfare of its people. However, the power of this economy needs to be accompanied by a defense force to protect all the economic activities of society.Keywords: Defense Budget Policy, Strategic Environmental Threat, State Ambition, Old Order, New Order, Order of Reform